IMPLEMENTATION OF ONLINE LEARNING AT SPECIAL SCHOOLS FOR CHILDREN WITH DISABILITIES DURING THE COVID-19 PANDEMIC SITUATION - Riksma Nurahmi Rinalti Akhlan (PEDAGOGIA, 2021)
Corona Virus Disease (Covid-19) that hit all parts of the world has a wide impact in various aspects of life, including education. As a special school teacher who often implements individual learning, it will be a challenge to implement online learning, it will even be a unique experience in changing the learning process from offline (face to face in class) to online (without face to face and outside the classroom). the biggest question is how the implementation of online learning can be carried out well considering the principles, rules and learning styles of children with disabilities that are unique and in very diverse ways. This research was conducted with a descriptive qualitative approach. The technique used is a survey technique. The distribution of questionnaires was carried out from June 4 to June 15, 2020 with a total of 560 respondents from 16 provinces in Indonesia. Online learning as the most possible alternative for the continuity of the learning process during the Covid-19 pandemic is basically responded to and responded to by both teachers and parents, even though teachers and parents realize that online learning is a new way full of knowledge and experience, so that it is still felt and considered ineffective, and even hopes to return to the conventional face-to-face system.